Chronic Arachidonic Acid Administration Decreases Docosahexaenoic Acid- and Eicosapentaenoic Acid-Derived Metabolites in Kidneys of Aged Rats. - Masanori Katakura (PLoS ONE, 2015)
Arachidonic acid (ARA) metabolites produced by cyclo-oxygenase and lipoxygenase are important mediators maintaining physiological renal function. However, the effects of exogenous ARA on kidney function in vivo remain unknown. This study examined the effects of long-term oral ARA administration on normal renal function as well as inflammation and oxidative stress in aged rats. In addition, we measured levels of renal eicosanoids and docosanoids using liquid chromatography-tandem mass spectrometry. Control or ARA oil (240 mg/kg body weight/day) was orally administered to 21-month-old Wistar rats for 13 weeks. Levels of plasma creatinine, blood urea nitrogen, inflammatory and anti-inflammatory cytokines, reactive oxygen species, and lipid peroxidation were not significantly different between the two groups. The ARA concentration in the plasma, kidney, and liver increased in the ARA-administered group. In addition, levels of free-form ARA, prostaglandin E2, and 12- and 15-hydroxyeicosatetraenoic acid increased in the ARA-administered group, whereas renal concentration of docosahexaenoic acid and eicosapentaenoic acid decreased in the ARA-administered group. Levels of docosahexaenoic acid-derived protectin D1, eicosapentaenoic acid-derived 5-, and 18-hydroxyeicosapentaenoic acids, and resolvin E2 and E3 decreased in the ARA-administered group. Our results indicate that long-term ARA administration led to no serious adverse reactions under normal conditions and to a decrease in anti-inflammatory docosahexaenoic acid- and eicosapentaenoic acid-derived metabolites in the kidneys of aged rats. These results indicate that there is a possibility of ARA administration having a reducing anti-inflammatory effect on the kidney.